Entre flores de cerejeiras e ipês: o florescer do entre-lugar e da identidade cultural em O Jardim Japonês, de Ana Suzuki - Pinto, Francisca Lailsa Ribeiro (2015)
This research conducts a study of the novel The Japanese Garden, of Brazilian Ana Suzuki, published in 1986, in order to verify the in-between where they mix different histories crossed by cultural identities in conflict. Based on the hypothesis that the mixed garden in the narrative, enables cultural assimilation meetings and resistance from Japanese immigrants and their descendants Japanese-Brazilians, the dissertation focuses on the hybrid space resulting from the diaspora meetings and simultaneously, the construction of the Japanese Garden of Yoneda character. To reflect on the cultural exchange between cherry blossoms and yellow trumpet trees, Japanese and Brazilian, that move and bloom the third bank, involved in conflict cultural situations of integration, draws on the theoretical foundation and critical concepts as in-between (Silviano Santiago), cultural identity (Stuart Hall), hybrid (Homi Bhabha), transculturation (Fernando Ortiz, Ángel Rama), and several other studies of the Japanese immigration to Brazil in order to point out elements of this common place that is Latin America.